PELATIHAN AYAT JURNAL PENYESUAIAN PERUSAHAAN DAGANG BAGI SISWA SISWI SMA - Dewi, Syanti (Jurnal Bakti Masyarakat Indonesia, 2024)
Learning about accounting is important, because it is important in daily financial management and needs to beapplied from an early age to high school students. In Economics subjects, material about Accounting is notdiscussed in detail and is only limited to students who choose the social sciences group. Apart from that, studentsalso think that accounting is a dif icult material so they tend not to be interested in this material. Based on theseproblems, our community service team held training activities with the aim of enriching students' knowledgeregarding accounting while changing the perception that accounting is a material that is dif icult to learn. Our teamhad the opportunity to explain the topic of the trading company accounting cycle, especially the part in preparingadjusting journal entries in November 2023. This training was given to students in classes X (ten), XI (eleven), andXII (twelve) through accounting extracurricular activities provided by Tarsisius High School 1. Training is carriedout in face-to-face form, starting with preparing teaching materials, providing theoretical explanations, discussingexample questions, then closing with a quiz with prizes which all Tarsisius 1 High School students take part in.Based on the results of the quiz and the good enthusiasm of the Tarsisius 1 High School students can be concludedthat the training activities have provided good results and have helped in increasing the students' understanding ofthe material. ABSTRAK: Pembelajaran mengenai ilmu akuntansi merupakan hal yang penting, karena berkaitan penting dalam pengelolaankeuangan sehari-hari dan perlu diterapkan sejak dini kepada siswa-siswi sekolah menengah. Pada mata PelajaranEkonomi, materi tentang akuntansi tidak dibahas secara terperinci dan hanya terbatas bagi siswa-siswi yang memilihrumpun ilmu sosial. Selain itu, siswa-siswi juga menganggap bahwa akuntansi adalah materi yang sulit sehinggamereka cenderung tidak tertarik dengan materi ini. Berdasarkan permasalahan tersebut, Tim pengabdian masyarakatkami, mengadakan kegiatan pelatihan dengan tujuan untuk memperkaya pengetahuan siswa-siswi terkait akuntansisekaligus mengubah persepsi bahwa akuntansi adalah materi yang sulit dipelajari. Tim kami mendapatkankesempatan untuk memaparkan topik mengenai siklus akuntansi perusahaan dagang terutama bagian dalampenyusunan ayat jurnal penyesuaian pada bulan November tahun 2023. Pelatihan ini diberikan kepada siswa-siswikelas X (sepuluh), XI (sebelas), hingga XII (dua belas) melalui kegiatan ekstrakurikuler akuntansi yang disediakanoleh SMA Tarsisius 1. Pelatihan dilaksanakan dalam bentuk tatap muka, dimulai dengan mempersiapkan bahan ajar,melakukan pemaparan teori, membahas contoh soal, lalu ditutup oleh kuis berhadiah yang diikuti seluruhsiswa-siswi SMA Tarsisius 1. Berdasarkan kuis serta antusiasme yang baik dari siswa-siswi SMA Tarsisius 1 dapatdisimpulkan bahwa kegiatan pelatihan memberikan hasil memuaskan dan telah membantu dalam meningkatkanpemahaman siswa-siswi terkait dengan materi tersebut.